1992
DOI: 10.1002/glia.440060106
|View full text |Cite
|
Sign up to set email alerts
|

Amoeboid and ramified microglia: Their interrelationship and response to brain injury

Abstract: Rio-Hortega's hypothesis that transiently appearing amoeboid microglia might become ramified microglia in the adult and that the latter could differentiate into brain macrophages in the event of brain damage could not be proved because of inherent limitations in existing techniques. The present investigation used a novel method of labelling the rat supraventricular amoeboid microglia with an enduring fluorescent marker, rhodamine B isothiocyanate, introduced intraperitoneally. Observation of their subsequent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 27 publications
5
75
3
Order By: Relevance
“…6). These events were described by del Rio-Hortega (1932), and received later support from morphological observations of intermediate forms between ameboid and rami®ed microglial cells (Ling, 1981;Perry et al, 1985;Leong and Ling, 1992;Wu et al, 1992Wu et al, , 1993Cuadros et al, 1994). The transformation of ameboid microglia into rami®ed microglia is now largely accepted (Perry and Gordon, 1988;Ling and Wong, 1993;Davis et al, 1994;Barron, 1995).…”
Section: Differentiation Of Microglial Cellsmentioning
confidence: 85%
“…6). These events were described by del Rio-Hortega (1932), and received later support from morphological observations of intermediate forms between ameboid and rami®ed microglial cells (Ling, 1981;Perry et al, 1985;Leong and Ling, 1992;Wu et al, 1992Wu et al, , 1993Cuadros et al, 1994). The transformation of ameboid microglia into rami®ed microglia is now largely accepted (Perry and Gordon, 1988;Ling and Wong, 1993;Davis et al, 1994;Barron, 1995).…”
Section: Differentiation Of Microglial Cellsmentioning
confidence: 85%
“…These cells, which exhibit features indicative of phagocytosis and which share common characteristics with their monocytic precursors (Yee et al, 1990;Ling et al, 19921, would seem likely candidates to become activated and proliferate after injury. However, recent work showed that ameboid cells do not migrate to the site of a stab wound cortical injury in the newborn brain (Leong and Ling, 1992) and that the major cell type responding to neonatal brain injury is the bloodborne phagocyte (Milligan et al, 1991). These findings, together with previous studies showing vascular sprouting in the middle layers of the 7-day-old rat neocortex (Hurley and Streit, 1991), the immaturity of the rat blood-brain barrier until 12 days after birth (Xu et al, 19931, and a blood-brain barrier disruption during the first 24 hours following the injection of an excitotoxin (Andersson et al, 1991a), support the possibility that most of the increase in tomato lectin-positive cells, seen at 3 days after the lesion, is due to a peripheral monocytic recruitment.…”
Section: Pattern Of Microglial Responsementioning
confidence: 98%
“…Third, there are the amoeboid microglial cells, known also as ''gitter'' or ''reactive'' microglia. These amoeboid cells have been described in the cerebral white matter, particularly in the corpus callosum, of the developing brain (Ling, 1976;Imamoto and Leblond, 1978;Valentino and Jones, 1981;Innocenti et al, 1983a,b;Leong et al, 1983;Lent et al, 1985;Boya et al, 1991;Chugani et al, 1991;Ling et al, 1991;Milligan et al, 1991a,b;Leong and Ling, 1992). These cells are of blood monocyte lineage and immigrate into the white matter from the vascular system during late embryonic and early postnatal life (Imamoto and Leblond, 1978;Ling et al, 1980Ling et al, , 1982Perry et al, 1985;Perry and Gordon, 1988;Boya et al, 1991;Chugani et al, 1991;Milligan et al, 1991a,b;Leong and Ling, 1992).…”
mentioning
confidence: 96%